The hotel industry in Spain during the first half of the twentieth century, 1900–1959 - Fernández-Paradas, Mercedes; Larrinaga Rodríguez, Carlos (Routledge Taylor & Francis Group, 2021)
The objective of this article is to analyse the evolution of the hotel sector in Spain in the first half of the twentieth century. More specifically, it seeks to study the tourist hotel industry within the Spanish tourism system which began to take shape during these years, marked by different political and economic contexts. Therefore, this tourist hotel industry is studied within the development of the tourism sector during these years in Spain. By the beginning of the twentieth century, tourism was understood as a social practice and it was an industry that was gaining importance within the Spanish economy.
Keywords: Hoteles y pensiones - Historia - España - S. XX; Hotel business; Tourist business; Tourist industry; Tourism; Spain; 1900 –1959